2013
DOI: 10.1007/s11130-013-0355-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Coffee Brew in Metabolic Syndrome and Type 2 Diabetes

Abstract: This study aimed to evaluate the effect of coffee drinking on clinical markers of diabetes and metabolic syndrome in Zucker rats. Diabetic Zucker rats with metabolic syndrome and control Zucker rats were used for in vivo tests. The animals received daily doses of coffee drink by gavage for 30 days. After the treatment, the levels of glucose, triglycerides, total cholesterol and fractions, creatinine, uric acid, activity of aspartate aminotransferase and alanine aminotransferase were evaluated. Urea and creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 15 publications
1
14
0
4
Order By: Relevance
“…These data provide evidence of the beneficial modification of microbiota composition by the diets supplemented with phenolic acids from coffee, which was also observed by Rao et al [23]. The inclusion of CGAs inside the molecules of β-cyclodextrin increased their bioavailability because of the limited interactions with the other components of the diet and bread [13, 17, 25]. …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…These data provide evidence of the beneficial modification of microbiota composition by the diets supplemented with phenolic acids from coffee, which was also observed by Rao et al [23]. The inclusion of CGAs inside the molecules of β-cyclodextrin increased their bioavailability because of the limited interactions with the other components of the diet and bread [13, 17, 25]. …”
Section: Resultssupporting
confidence: 77%
“…CGAs exhibit a broad range of biological activities: anti-thrombotic, anti-inflammatory, hypoglycemic and antioxidant [710]. CGAs decrease the risk of several oxidative stress-related diseases, including atherosclerosis, some kinds of cancer and type 2 diabetes [1113]. Because the concentration of CGAs is significantly reduced by roasting, these compounds should be extracted from green coffee.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that coffee supplementation attenuated the onset of common MetS features as well as and the development of NAFLD in experimental animals, without significant effects of abdominal obesity . Similarly, a study conducted in diabetic Zucker rats affected by the MetS showed that daily doses of coffee drink given by gavage for 30 days resulted in significant hypoglycaemic and hypolipidaemic effects, ultimately protecting against the development of an adverse metabolic profile …”
Section: Resultsmentioning
confidence: 84%
“…Three experimental animal studies investigated the effects of coffee in the MetS, whereas five examined whether experimental coffee intake may modulate the risk of fatty liver infiltration …”
Section: Resultsmentioning
confidence: 99%
“…Because of its impact on the pro-inflammatory state, the role of coffee consumption has been explored both in NAFLD and MS (Table 2) [60]. Coffee supplementation attenuates the expected onset of an adverse metabolic pattern in animals fed high-fat diets [52,53].…”
Section: Nalfd: the Liver At The Centermentioning
confidence: 99%